Addressing Barriers to Inclusion: Challenges and Recommendations for Inclusive Primary Education in Bangladesh - Sarker, Anupom; Unzum, Towsif (Journal of Education Review Provision, 2023)
Despite policy commitments to inclusive education, significant barriers hinder its true realization in Bangladesh, particularly at the primary level. This research utilizes secondary data analysis to comprehensively identify and examine these challenges, drawing insights from official reports, academic literature, and stakeholder interviews. The study investigates four primary domains: policy and infrastructure, teacher preparedness and practices, attitudes and awareness, and accessibility and support mechanisms. Findings reveal systemic limitations in infrastructure and resource allocation, inadequate teacher training in inclusive pedagogies, persisting negative attitudes towards diverse learners, and insufficient support services for children with disabilities and marginalized backgrounds. Drawing on these insights, the paper proposes multi-pronged recommendations across each domain, advocating for: 1) strengthened policy frameworks and resource allocation, 2) comprehensive teacher training in inclusive practices and differentiated instruction, 3) community-based awareness campaigns on inclusion and diversity, and 4) improved accessibility measures in schools and learning materials. The research emphasizes the need for collaborative efforts at national, local, and school levels to dismantle identified barriers and create a truly inclusive primary education system in Bangladesh, ensuring equitable access and quality learning for all children.